Liraglutide Activates Glucagon-Like Peptide 1 Receptor to Attenuate Hyperglycemia through Endogenous Beta-Endorphin in Diabetic Rats - Kai-Chun Cheng; Ying-Xiao Li; Po-Chuen Shieh; Juei-Tang Cheng; Chia-Chen Hsu (Pharmaceuticals, 2020)
Liraglutide, an acylated analog of glucagon-like peptide 1 (GLP-1), could improve glycemic control in diabetes. Moreover, endogenous opioid peptides play a role in blood sugar regulation. Since GLP-1 receptors are also expressed in extra-pancreatic tissues, this study investigates the effect of liraglutide on endogenous opioid secretion in type 1-like diabetes. The endogenous opioid level was determined by enzyme-linked immunosorbent assay. The direct effect of liraglutide on endogenous opioid secretion was determined in the isolated adrenal medulla. Acute treatment with liraglutide dose-dependently attenuated hyperglycemia, and increased the plasma opioid neuropeptide, beta-endorphin (BER) levels in diabetic rats. These effects have been blocked by GLP-1 receptor antagonist, naloxone. Additionally, the effects of liraglutide were markedly reduced in adrenalectomized diabetic rats. In the isolated adrenal medulla, liraglutide induced BER secretion and increased the BER mRNA levels. Subcellular effects of liraglutide on the adrenal gland were further identified to mediate through the exchange proteins directly activated by cAMP, mainly using the pharmacological blockade. After repeatedly administering liraglutide, metabolic changes in diabetic rats were investigated, and genes associated with gluconeogenesis in the liver were downregulated. Naloxone pretreatment inhibited these effects of liraglutide, indicating the involvement of endogenous opioids. The present study indicated that liraglutide had an acute effect of reducing hyperglycemia by regulating endogenous opioid BER and modifying the glucose homeostasis.